Safety of peginterferon alfa-2a (40KD) treatment in patients with chronic hepatitis B infection: An observational, multicenter, open label, non-interventional study in Turkish patients - Tozun, Nurdan; Sezgin, Orhan; Gulsen, Murat; Kacar, Sabite; Yenice, Necati; Yilmaz, Serif; Bagci, Sait (Aves, 2012)
Background/aims: Pegylated alfa interferon is the only immunomodulatory drug licensed for hepatitis B. We evaluated the safety and tolerability of peginterferon alfa-2a (40KD) in patients with chronic hepatitis B. Materials and Methods: A total of 113 chronic hepatitis B patients under peginterferon alfa-2a (40KD; 180 mu g/week) treatment were included in this multicenter, open label, non-interventional study, and 66 patients completed the follow-up period. Vital signs, physical examination and laboratory findings, concomitant medications, and adverse events were recorded. A Quality of Life questionnaire (Short Form-36) was performed twice, at the beginning and at the end of the study. Results: There was no significant difference between initial and last visits in terms of physical examination findings and Short Form-36 scores. A total of 27 adverse events were reported in 15 patients (22.7%), with most of them being mild in intensity (70.4%). The rates of the adverse events were similar in the monotherapy and combination therapy groups (peginterferon alfa-2a + lamivudine, peginterferon alfa-2a + adefovir or peginterferon alfa-2a + entecavir therapy groups), at 23.7% and 14.3%, respectively. The dosage of peginterferon had to be reduced in 3 patients (4.5%) due to thrombocytopenia. Overall patient compliance to treatment was detected as 85.9%. Conclusions: Based on the lack of serious adverse events and absence of impairment in Quality of Life, peginterferon alfa-2a (40KD, 180 mu g/week, subcutaneously) treatment for 48 weeks led to a high level of patient compliance and was associated with a high degree of safety and tolerability for the treatment of adult patients with chronic hepatitis B in real-life practice.
Keywords: Peginterferon alfa-2a; HBV infection; safety; patient compliance; tolerability; real-life practice